IDNLearn.com: Your trusted platform for finding reliable answers. Ask anything and receive immediate, well-informed answers from our dedicated community of experts.
Sagot :
We need to solve the given equation and then find the sum of all possible solutions.
The equation is:
[tex]\frac{18-3w}{w+6}=\frac{w^2}{w+6}[/tex]Notice that the denominator on both sides is w+6. Since the denominator can't be zero, we have:
[tex]\begin{gathered} w+6\ne0 \\ \\ w\ne-6 \end{gathered}[/tex]Thus, -6 can't be a solution.
Now, we can solve the equation by rewriting it as
[tex]\begin{gathered} \frac{18-3w}{w+6}\cdot(w+6)=\frac{w^2}{w+6}\cdot(w+6) \\ \\ 18-3w=w^{2} \\ \\ w^{2}+3w-18=0 \end{gathered}[/tex]Now, we can use the quadratic formula to solve it:
[tex]\begin{gathered} w=\frac{-3\pm\sqrt[]{3^{2}-4(1)(-18)}}{2(1)} \\ \\ w=\frac{-3\pm\sqrt[]{9+72}}{2} \\ \\ w=\frac{-3\pm\sqrt[]{81}}{2} \\ \\ w=\frac{-3\pm9}{2} \\ \\ w_1=\frac{-3-9}{2}=-6\text{ (this solution is not possible)} \\ \\ w_2=\frac{-3+9}{2}=3 \end{gathered}[/tex]Therefore, the only possible solution is 3. And the sum of all possible solutions is 3.
We value your presence here. Keep sharing knowledge and helping others find the answers they need. This community is the perfect place to learn together. Thank you for visiting IDNLearn.com. We’re here to provide clear and concise answers, so visit us again soon.